2012
DOI: 10.1117/12.915829
|View full text |Cite
|
Sign up to set email alerts
|

An innovative approach to achieve re-centering and ductility of cement mortar beams through randomly distributed pseudo-elastic shape memory alloy fibers

Abstract: Fibers can play a major role in post cracking behavior of concrete members, because of their ability to bridge cracks and distribute the stress across the crack. Addition of steel fibers in mortar and concrete can improve toughness of the structural member and impart significant energy dissipation through slow pull out. However, steel fibers undergo plastic deformation at low strain levels, and cannot regain their shape upon unloading. This is a major disadvantage in strong cyclic loading conditions, such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…SMAs, such as Nickel-Titanium alloys [14,15] or Copper-Alluminium-Manganese alloys [16][17][18][19], feature shape memory effect and superelasticity. SMAs have been studied as partial replacement of steel rebars [20][21][22][23][24][25][26][27][28][29], the confinement for column [30][31][32][33][34][35][36][37], fibers [38][39][40][41][42], and external devices and dampers [43][44][45][46][47][48][49][50][51] for concrete structures. These studies showed that with particular prestrain, SMA can improve energy dissipation capacity of RC members while reducing residual crack width and deformation.…”
Section: Introductionmentioning
confidence: 99%
“…SMAs, such as Nickel-Titanium alloys [14,15] or Copper-Alluminium-Manganese alloys [16][17][18][19], feature shape memory effect and superelasticity. SMAs have been studied as partial replacement of steel rebars [20][21][22][23][24][25][26][27][28][29], the confinement for column [30][31][32][33][34][35][36][37], fibers [38][39][40][41][42], and external devices and dampers [43][44][45][46][47][48][49][50][51] for concrete structures. These studies showed that with particular prestrain, SMA can improve energy dissipation capacity of RC members while reducing residual crack width and deformation.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, concrete or cement composites with shape memory alloys (SMAs) are proposed and considered as smart composites that can generate recovery stress of SMAs due to the shape memory effect (SME) to provide pre-stress or crack-curing capacity in cement composites. This has been investigated by many studies (Czaderski et al 2014, Choi et al 2014a, Shajil et al 2012.…”
Section: Introductionmentioning
confidence: 99%